Addressing Climate Change Through Sport - Bas, D.; Haghian, P. Z.; Hoagland, S. (2022)
Climate change is one of the most pressing issues of our times. Sport plays an important role as part of the solution. Sport is a key social platform that can reach and influence millions of peoples worldwide and raise awareness on climate change, promote a culture in favour of climate action, and champion sustainable behaviours. The sport sector can contribute to tackle climate change by reducing sport organizations's climate footprint while governments and international organizations facilitate this goal by setting right policies and guidelines.